Modulacija povezovanja eksonov s protismiselnimi oligonukleotidi kot terapevtska strategija - Bratkovič, Tomaž (Farmacevtski vestnik, 2019)
Many gene diseases arise from mutations responsible for incorrect primary transcript (pre-mRNA) processing. RNA splicing (exon joining and intron removal) is catalyzed by a ribonucleoprotein complex termed the spliceosome, and regulated by numerous protein factors binding to pre-mRNA regulatory sequences, thereby either promoting or suppressing specific exon inclusion. In order to achieve therapeutic results, the binding of protein factors to pre-mRNA can be blocked by synthetic complementary (antisense) oligonucleotides. In turn, the splicing profile (i.e. exon usage) is changed, leading to modified protein product structure and function. Recently, European Medicinal Agency (EMA) and the US Food and Drug Administration (FDA) have approved the first two antisense oligonucleotide drugs that modulate splicing for the treatment of spinal muscular atrophy and Duchenne muscular dystrophy. Here, the therapeutic potential and mechanisms of action of antisense oligonucleotide splicing modulators are reviewed, and their limitations are discussed.
Keywords: Bolezni; Duchennova mišična distrofija; Genetika; povezovanje eksonov; protismiselni oligonukleotidi; spinalna mišična atrofija